Aqueous Ion Battery Systems Using Sodium Vanadium Phosphate Stabilized by Titanium Substitution. (1st January 2015) - Mason, Chad W.; Lange, Felix
Abstract : Na3 V2 (PO4 )3 is a popular sodium-ion intercalating cathode material. It degrades in aqueous electrolytes, though. By substitution of half of the vanadium with titanium, the related compound, Na2 VTi(PO4 )3, was obtained. Three distinct sets of experiments were employed to qualify the potential utility of this material in various aqueous ion battery applications, including sodium and zinc ion. High levels of cycle stability were observed in neutral sodium-containing electrolyte, but less-so in zinc-containing electrolyte. At the end, pouch cells were built with both activated carbon and NaTi2 (PO4 )3 anode materials, demonstrating practical capabilities of systems utilizing these materials.